2021
DOI: 10.3390/f12020230
|View full text |Cite
|
Sign up to set email alerts
|

Performance and Phenotypic Stability of Norway Spruce Provenances, Families, and Clones Growing under Diverse Climatic Conditions in Four Nordic Countries

Abstract: Genetic variation and phenotypic stability in Norway spruce were studied based on provenances, families, and clones planted in trials at 12 sites in four Nordic countries. The families were generated in a factorial cross between 10 parents of Norwegian origin and 10 parents of Eastern European origin, and the clones were propagated from seedlings within 20 of the same families. Traits analyzed were survival, proportion of trees with stem defects, and tree heights. Stability was analyzed by regression analyses … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 12 publications
(39 reference statements)
1
2
0
Order By: Relevance
“…They showed that for height growth, genetic variation is lower in populations exposed to severe cold extreme events. This finding was also reported by Skrøppa and Steffenrem (2021) in a study involving Nordic, Central, and Eastern European provenances of Norway spruce. Archambeau et al (2021) additionally showed that genetic variation from populations of genetically mixed provenances was not influenced by gene flow that might be thought to increase genetic variation.…”
Section: Extreme Eventssupporting
confidence: 85%
“…They showed that for height growth, genetic variation is lower in populations exposed to severe cold extreme events. This finding was also reported by Skrøppa and Steffenrem (2021) in a study involving Nordic, Central, and Eastern European provenances of Norway spruce. Archambeau et al (2021) additionally showed that genetic variation from populations of genetically mixed provenances was not influenced by gene flow that might be thought to increase genetic variation.…”
Section: Extreme Eventssupporting
confidence: 85%
“…A similar trend has occurred in Douglas-fir breeding in France, which currently prioritises phenology, architecture, branching patterns, and wood density over growth (Bastien et al 2021). In Nordic breeding programmes of Norway spruce and Scots pine, increased adaptive performance and phenotypic plasticity across environments (Danell 1993, Skrøppa & Steffenrem 2021) are now given more attention.…”
Section: Breeding Objectives and Selected Traitsmentioning
confidence: 82%
“…This indicates that meteorological factors have a certain impact on growth [32,33]. The correlation of meteorological factors and growth rhythm can be a useful supplement when selecting superior and stable genotypes [34].…”
Section: Introductionmentioning
confidence: 99%